1986
DOI: 10.1073/pnas.83.19.7137
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of laminin receptor mRNA in various human carcinoma cells that have different abilities to bind laminin.

Abstract: The human laminin receptor was purified and molecularly cloned to investigate its biosynthetic regulation. Laminin receptor from normal and neoplastic tissue was preparatively affinity purified to homogeneity based on the high affinity of the receptor for laminin. The apparent molecular weight of the receptor from different carcinoma sources and from normal placental tissue is in the range of 68-72 kDa. Isoelectric focusing and two-dimensional gel electrophoresis indicated that the receptor protein consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(177 citation statements)
references
References 29 publications
8
169
0
Order By: Relevance
“…In addition to directly affecting cell-ECM interaction through binding laminin, LR has also been reported to interact with ␣6␤4 integrin and regulate or stabilize the attachment of cells to laminin through integrin (Ardini et al, 1997). The expression level of LR in cancer cells is correlated with abilities to bind laminin (Wewer et al, 1986), which could be due to either the binding of LR directly to laminin or indirectly by affecting integrin-laminin interaction. In addition, LR has been reported to have other functions.…”
Section: A Likely Role Of Lr Cleavage By St3 During Intestinal Remodementioning
confidence: 94%
“…In addition to directly affecting cell-ECM interaction through binding laminin, LR has also been reported to interact with ␣6␤4 integrin and regulate or stabilize the attachment of cells to laminin through integrin (Ardini et al, 1997). The expression level of LR in cancer cells is correlated with abilities to bind laminin (Wewer et al, 1986), which could be due to either the binding of LR directly to laminin or indirectly by affecting integrin-laminin interaction. In addition, LR has been reported to have other functions.…”
Section: A Likely Role Of Lr Cleavage By St3 During Intestinal Remodementioning
confidence: 94%
“…An animal cell surface protein, the 67-kD high-affinity receptor for the ECM adhesion protein laminin (wewer et al, 1986), is immunologically related to a 33-to 37-kD polypeptide (Rao et al, 1989) of the translational machinery (Auth and Brawerman, 1992). A partial amino acid sequence obtained from a CNBr fragment of the laminin receptor is identical to the sequence of the 33-to 37-kD protein (Wewer et al, 1986). For both PVNl and the 67-kD laminin receptor, more sequence information is needed to ascertain the relationship between these proteins and the proteins of the translational machinery.…”
Section: Pvn1 Is Related To Ef-1amentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8] Furthermore, recent microarray expression profiling and proteomic studies have confirmed this established correlation, for instance see Refs. 9 and 10.…”
mentioning
confidence: 78%